Evaluation of actin as a reference for quantitative gene expression studies in Emiliania huxleyi (Prymnesiophyceae) under ocean acidification conditions. Issue 2 (4th March 2021) - Puig-Fàbregas, Júlia; Alcaraz-Rocha, Paulo; Fernández, Emilio; Rotllant, Josep; Sobrino, Cristina
ABSTRACT: Gene expression studies of marine phytoplankton under ocean acidification conditions are frequently based on relative measurements, with actin commonly used as a reference gene. Evidence from other organisms suggests that actin gene expression may be regulated by environmental conditions, compromising the role of actin as a reference gene. In this work the reliability of actin as a reference gene for ocean acidification experimental conditions (high CO2 vs low CO2 ) in two different metabolic states (acclimated metabolism vs perturbed metabolism) for the coccolithophore Emiliania huxleyi was tested. The transcriptional response of the actin ( act ) is compared with the expression of specific target genes associated with inorganic carbon uptake (α-carbonic anhydrase: αca1 ) and assimilation (RuBisCO: rbcL ), which was regulated under the experimental conditions. Our results showed act expression instability in experimental conditions, evidencing that act is not a reliable reference gene for studies assessing the effect of ocean acidification on Emiliania huxleyi . Furthermore, when the act -based normalization was quantitatively tested, rbcL and αca1 expression were compromised, leading us to conclude that absolute gene expression quantification should be considered as a potentially reliable alternative for studying gene expression under ocean acidification conditions.